Hepatitis E virus in blood donors in England, 2016 to 2017: from selective to universal screening - Harvala, Heli (Euro Surveill, 2019)
INTRODUCTION: Hepatitis E virus (HEV), the most common cause of acute hepatitis in many European countries, is transmitted through consumption of processed pork but also via blood transfusion and transplantation. HEV infection can become persistent in immunocompromised individuals. AIM: We aimed to determine the incidence and epidemiology of HEV infection in English blood donors since the introduction of donation screening in 2016. METHODS: Between March 2016 and December 2017, 1,838,747 blood donations were screened for HEV RNA. Donations containing HEV RNA were further tested for serological markers, RNA quantification and viral phylogeny. Demographics, travel and diet history were analysed for all infected donors. RESULTS: We identified 480 HEV RNA-positive blood donations during the 22-month period, most (319/480; 66%) donors were seronegative. Viral loads ranged from 1 to 3,230,000 IU/ml. All sequences belonged to genotype 3, except one which likely represents a new genotype. Most viraemic donors were over 45 years of age (279/480; 58%), donors aged between 17 and 24 years had a seven-times higher incidence of HEV infection than other donors between March and June 2016 (1:544 donations vs 1:3,830). HEV-infected blood donors were evenly distributed throughout England. Screening prevented 480 HEV RNA-positive blood donations from reaching clinical supply. CONCLUSION: HEV screening of blood donations is a vital step in order to provide safer blood for all recipients, but especially for the immunosuppressed. The unusually high rates of HEV infection in young blood donors may provide some insight into specific risks associated with HEV infection in England.